THE INFLUENCE OF LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE OF MUTIA SARI GENERAL HOSPITAL, BENGKALIS REGENCY ACCORDING TO SHARIA MANAGEMENT PERSPECTIVES - Henry, Henry Martin Adriansyah; Dedi Hermanto (Journal of Islamic Banking, Economics and Finance, 2025)
This study aims to determine the effect of Leadership Style on the Performance of Employees of Mutia Sari General Hospital, Bengkalis Regency. The method used is quantitative with data collection techniques through questionnaires to several employees of Mutia Sari General Hospital. Data analysis was carried out by testing validity, reliability, classical assumptions, simple linear regression, hypothesis testing, determination tests (R²), and t-tests. The results of the validity and reliability tests indicate that all research instruments are valid and reliable. The results of the classical assumption test prove that the data is normally distributed. The results of simple linear regression and hypothesis testing indicate that Leadership Style has a positive effect on employee performance. The coefficient of determination (R²) of 0.939 indicates that job training contributes 93.9% to improving performance, while the rest is influenced by other factors. The t-test produces a significant value (Sig.> 0.05), so it can be concluded that Leadership Style has a significant effect on employee performance at Mutia Sari General Hospital. Thus, Leadership Style is an important factor in improving Employee Performance.